Effect of Additional Cytoplasm of Cloned Embryo on In Vitro Developmental Competence and Reprogramming Efficiency in Mice - Song, Seok-Hwan; Oh, Seon-Hwa; Xu, Lianguang; Lee, Kyeong-Lim; Hwang, Ji-Yoon; Joo, Myeong-Don; Kong, Il-Keun (Cellular reprogramming, 2020)
Somatic cell nuclear transfer (SCNT) is an important technique for biological science research. Cytoplasm injection cloning technology (CICT) was developed to improve the reprogramming efficiency as well as to overcome the limitations of SCNT. CICT uses an additional cytoplasm fused with an enucleated oocyte to restore the cytoplasmic volume of the cloned embryo, and this method could improve the reprogramming efficiency of the cloned embryo. In this study, we show that CICT can be adapted to mouse species to overcome the inefficiency of the SCNT method. In this study, results indicate that the two-cell embryo and blastocyst rates of cloned embryos with the use of the CICT method were significantly higher ( < 0.05) than that of the SCNT method (96.6% ± 1.1% vs. 86.7% ± 6.0%, 29.5% ± 2.6% vs. 22.1% ± 3.0%, respectively). Furthermore, the apoptotic cell number per blastocyst was significantly lower in the CICT group than that in the SCNT group (1.7 ± 0.2 vs. 2.9 ± 0.3, < 0.05). Moreover, the acH3K9/K14 expression level in the CICT group was greater than that of the SCNT group ( < 0.05), and the relative acH3K56 level in the CICT group was significantly ( < 0.05) higher than that in the SCNT group. These results indicate that CICT helps improve the developmental competence and quality of cloned embryos.